Gospel Jesuses and other nonhumans : Biblical criticism post-poststructuralism - Moore, Stephen D., 1954- (Semeia studies, 2017)
"The current global ecological crisis has prompted a turn to the nonhuman in critical theory. This book breaks new ground in biblical studies as the first to bring nonhuman theory to bear on the Gospels and Acts. Nonhuman theory, a confluence of several of the main theoretical streams that have issued forth since the heyday of high poststructuralism, includes affect theory, posthuman animality studies, critical plant studies, object-oriented new materialisms, and assemblage theory. Nonhuman theory dismantles and reassembles the Western concept of "the human" that coalesced during the Enlightenment and testifies to other conceptions of the human and of the nonhuman, not least those found in the canonical Gospels and Acts. Stephen D. Moore's exegetical explorations and defamiliarizations of these overly familiar texts and excavations of their incessantly erased strangeness are the central feature of this provocative book."--